Dual‐Electromagnetic Field Enhancements through Suspended Metal/Dielectric/Metal Nanostructures and Plastic Phthalates Detection in Child Urine. Issue 2 (13th November 2019) - Hu, Junzheng; Yu, Huikang; Su, Guangxu; Song, Boxiang; Wang, Jie; Wu, Zhenqiu; Zhan, Peng; Liu, Fanxin; Wu, Wei; Wang, Zhenlin
Abstract: Plasmonic nanostructures exhibit intriguing optical properties due to spectrally selective plasmon resonance and thus have broad applications, including biochemical sensing and photoelectric detections. However, excited plasmons are often strongly influenced by the substrates supporting the metallic nanostructures, which not only weakens the intrinsic plasmon coupling effect, but also results in a great reduction of optical near‐field enhancement. Here, a plasmonic nanostructure combining collapsible Au‐nanofingers with selective‐etching that enables Au to be suspended is demonstrated, thus avoiding the undesirable influence of the substrates on the local near‐field distribution and forming symmetric electromagnetic‐field enhancements at both the top and bottom surfaces. The polymer support of the Au‐nanofingers is selectively etched by oxygen plasma, while the Au‐cap retains its original size. After an ultrathin dielectric coating is applied on the Au‐nanofingers, suspended Au‐caps with extremely small dielectric gaps are formed via the collapse of neighboring Au‐nanofingers by exposing them to ethanol. These nanostructures can provide a surface‐enhanced Raman scattering (SERS) enhancement of up to ≈10 9, which is nearly twice that in the nonsuspended system. As a highly active SERS substrate, the label‐free detection of low‐concentration harmful plastic phthalates in a child's urine without any pretreatment is successfully demonstrated, which suggests that this method is suitable for medical prediagnosis. Abstract : A suspended gap‐plasmonic nanostructure is created through the collapsible Au‐nanofingers and selective‐etching, which avoids the undesirable influence of the substrates on the local near‐field distribution and forms symmetric electromagnetic ‐field enhancements at both the top and bottom surfaces. The resulting label‐free surface‐enhanced Raman scattering detection of low‐concentration harmful plastic phthalates in child urine without any pretreatment is successfully demonstrated.